2021
DOI: 10.1590/0001-3765202120190988
|View full text |Cite
|
Sign up to set email alerts
|

Parasites in Leporinus macrocephalus (Anostomidae) of four fish farms from the western Amazon (Brazil)

Abstract: This study evaluated the presence of metazoan parasites in Leporinus macrocephalus from four fi sh farms from the western Amazon (Brazil). In 160 fi sh examined, prevalence was 61.9%, and parasites found were: Urocleidoides paradoxus, Urocleidoides eremitus, Tereancistrum parvus, Jainus leporini, Procamallanus (Spirocamallanus) inopinatus, Rhabdochona (Rhabdochona) acuminata, Dolops discoidalis and Ergasilus sp., but U. paradoxus was the dominant parasite. Jainus leporini and Ergasilus sp. occurred only in L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The present study evaluated parasite indices of 57 host species and, for the first time, the parasite characteristics of 36 host fish were reported, which, in addition to helping to increase information on the infracommunities of endoparasites in an environment, can also provide data for studies on evolution, distribution and ecology. Few studies collected more than ten hosts with field campaigns in a single region (Baia et al ., 2018; Negreiros et al ., 2021) and some parasite fauna checklists were studies involving several collections and years of research (Lehun et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study evaluated parasite indices of 57 host species and, for the first time, the parasite characteristics of 36 host fish were reported, which, in addition to helping to increase information on the infracommunities of endoparasites in an environment, can also provide data for studies on evolution, distribution and ecology. Few studies collected more than ten hosts with field campaigns in a single region (Baia et al ., 2018; Negreiros et al ., 2021) and some parasite fauna checklists were studies involving several collections and years of research (Lehun et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Currently for the Western Amazon, some studies have reported a high diversity of endoparasites, but a few host species from natural environments were analysed in these environments, such as Pimelodus blochii Valenciennes, 1840, Arapaima gigas Schinz, 1822, Cichla melaniae Kullander & Ferreira, 2006, Calophysus macropterus Lichtenstein, 1819, Phractocephalus hemioliopterus Bloch & Schneider, 1801 and Leporinus macrocephalus Garavello & Britski, 1988(Cavalcante et al, 2017Baia et al, 2018;Negreiros et al, 2018Negreiros et al, , 2019Negreiros et al, , 2021. Such studies revealed a high richness, mainly Nematoda and Digenea, where new species and geographical distributions of these endoparasites were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Farmed in commercial fish farms, these fish are routinely stressed by intensive production management practices, leading to the emergence of parasitic diseases that naturally occur in the aquatic environment. Hence, parasitic diseases are most common in the farming of these fish species and are among the factors that strongly interfere with their growth (Martins et al, 2017;Negreiros & Tavares-Dias, 2019;Negreiros et al, 2021). Among the main taxa of disease-causing parasites in P. brachypomus (Negreiros & Tavares-Dias, 2019) and M. macrocephalus (Martins et al, 2002(Martins et al, , 2017Negreiros et al, 2021Negreiros et al, , 2022 are helminths monogeneans.…”
Section: Introductionmentioning
confidence: 99%